Paul Bowles's first insight into the interaction with North-African alterity in "Tea on the Mountain" - Gomes, Fernando (2013)
Abstract In "Tea on the Mountain", Paul Bowles evokes the Tangier of the early thirties (twentieth century), a city politically, socially, financially and sexually attractive to Westerners. This paper aims to demonstrate that apart from depicting the ineffectualness of cultural encounter, due to value judgments, western as well as native, that pervert the essence of the alterity, Bowles testifies and condemns the ruinous effects of colonization and the destructive westernization of the Arab culture. The paper also intends to show that, although not being paradigmatic of Bowles' mastery in writing fiction, this short story foreshadows his subsequent work: the attraction of the unknown; the solitude of the contemplative mind in a culture that is never fully identified and understood; the longing for, as well as the impossibility of, a genuine relationship between cultures.